Nigerian Library and Information Science Academics Patronising Predatory Journals: A Call for Re-direction to Publishing in Highly Rated Journals - TELLA, Adeyinka (Revista Cubana de Información en Ciencias de la Salud, 2025)
Goal: This paper examined Nigerian Library and Information Science academics’ patronage of predatory journals with a call for re-direction and re-orientation to publishing in high-impact journals. Methods: A qualitative approach was adopted using interviews, document analysis, and analysis of journals websites, and databases. Thirty Library and Information Science scholars selected from five library schools in South-west, Nigeria represent the sample for the study. Six research questions were answered in the study. Results: The findings reveal that Library and Information Science educators publish to update knowledge, establish themselves as a researcher of repute, promotion, and gain recognition in their discipline, fund project participation, and mobility, and increase feasibility. The awareness of predatory journals and publishers among Library and Information Science academics is very low and one of the reasons for patronising predatory journals and publishers. Predatory journals are perceived as journals that collect money for publication at the expense of scholarship, deceitful journals that do not follow scholarly communication ethics, and journals that engage in an aggressive advert to lure academics to publish in them. Library and Information Science academics publish in predatory journals to get a promotion without delay; because of dwindling scholarship; a reduction in the conduct of quality research; and the inability to endure the rigour of publishing in high-impact journals. Conclusion: Library and Information Science scholars were encouraged to stop patronising predatory journals and publishers and should also stop publishing for promotion rather than to become established scholars or academics of special repute.